Amyotrophic lateral sclerosis and osteoporosis: a two-sample Mendelian randomization study - Li, Junhong; Ma, Cong; Huang, Hui; Liao, Hui (Frontiers in Aging Neuroscience, 2023)
Background: A few of observational studies revealed that amyotrophic lateral sclerosis (ALS) was tightly connected with osteoporosis. However, results of previous studies were inconsistent and the causal effect of ALS on osteoporosis has not been investigated.To do so, the two-sample mendelian randomization (MR) method was employed to estimate the causality.The instrumental variables (IVs) for ALS were selected from one GWAS summary dataset (27,205 ALS cases and 110,881 controls), bone mineral density (BMD) in femoral neck (FN), lumbar spine (LS) and forearm, extracted from another largescale GWAS summary database (53,236 cases) were used as phenotypes for osteoporosis. Random-effects inverse variance weighted (IVW), MR Egger, weighted median, simple mode, and weighted mode were conducted to evaluate the causality.Sensitivity analyses were further performed to explore the heterogeneity and pleiotropy.Results: 10 qualified SNPs were finally selected as proxies for ALS. The results of random effects IVW showed that ALS has no causal effect on FN-BMD (beta: -0.038,